Performance comparison of machine learning and GPU accelerated solvers in high-fidelity simulation of Cambridge stratified flames - Min Zhang; Guanlin Dang; Runze Mao; Yuqing Cai; Ruixing Yang; Han Li; Zhi X. Chen (Fuel, 2026)

Asymmetric evolution of capturability of atmospheric water (CAW) across global arid and humid regions - Hou-Liang Lu; Hong-Ru Wang; Hui-Min Zuo; Han Zhou; Yu-Fei Jiao; Bill X. Hu (Journal of Hydrology, 2026)

Enhancing deep learning of ammonia/natural gas combustion kinetics via physics-aware data augmentation and scale separation - Ke Xiao; Yangchen Xu; Han Li; Zhi X. Chen (Fuel, 2026)

In vitro ibuprofen has gene regulatory and anti-inflammatory properties in peripheral blood mononuclear cells of individuals with infection-provoked neurodevelopmental disorders - Velda X. Han; Jessica P. Hayes; Brian Gloss; Ruwani Dissanayake; Xianzhong Lau; Erica Tsang; Hiroya Nishida; Melanie Wong; Shekeeb S. Mohammad; Shrujna Patel; Russell C. Dale (Inflammopharmacology, 2026)
Gene-environment interactions, leading to immune-brain cross-talk and neuroinflammation are increasingly recognised in neurodevelopmental disorders (NDDs), such as autistic regression and paediatric acute onset neuropsychiatric syndrome (PANS). Nonsteroidal anti-inflammatory drugs, including ibuprofen, provides relief to some neuropsychiatric symptoms, however, the therapeutic mechanisms are unclear. We describe the benefit of ibuprofen in 18 children (11 males, ages 5–20 years) with infection-provoked deteriorations compatible with PANS (16/18) or autistic regression (7/18), five met criteria for both. Ibuprofen was well tolerated and led to improved emotional control, obsessive–compulsive symptoms, and aggression during infection-related exacerbations or the chronic phase. Single-cell RNA sequencing (scRNA-seq) was performed on peripheral blood mononuclear cells (PBMCs) in two children and their respective age-, sex- matched controls, before and after 24 h of in vitro ibuprofen and/or paracetamol incubation. A total of 45,134 cells were included. At baseline in both cases, there was dysregulation of immune pathways (response to virus, cell killing) and downregulation of ribosomal and translational pathways. Ibuprofen reversed the pro-inflammatory state in both children with reversal of cell killing pathways (granzyme genes) in Case 1, and reversal of viral pathways (interferon genes) in Case 2. Ibuprofen also reversed translation pathways (ribosomal protein genes), and regulation of translation (including EIF genes). In vitro paracetamol produced similar but weaker effects than ibuprofen. Children with infection-provoked neurodevelopmental episodes have baseline transcriptional and immune dysregulation in peripheral immune cells. We show that ibuprofen has transcriptional and anti-inflammatory effects, and that scRNA-seq in vitro-based studies can inform disease-modifying therapies for individuals with NDDs.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Click Chemistry-Based Quantification of Extracellular Matrix Turnover for Drug Screening and Regenerative Medicine - Annie Porter; Songshan Fan; Ying Peng; Mengxi Lv; Yilu Zhou; Abdulaziz Alanazi; Lin Han; Liyun Wang; X. Lucas Lu (Annals of Biomedical Engineering, 2026)
Purpose To develop and validate a bioorthogonal labeling approach for quantifying ECM remodeling in living cell and tissue culture systems. Methods Strain-promoted azide-alkyne (SPAAC) reactions, or copper-free click chemistry, were used to fluorescently label newly synthesized glycan and protein matrix components. ECM synthesis and degradation was quantified in cartilage explants, human mesenchymal stem cells, and SKBR3 breast cancer cells under various external stimuli, including inflammation, mechanical stimulus, and drug treatment. Results The click chemistry method reliable quantified ECM turnover across platforms. It detected reduced glycan and protein synthesis after 24-hour inflammatory challenge and enabled longitudinal tracking of ECM degradation in cartilage explants. The technique demonstrated high sensitivity, measuring increased ECM deposition by ~ 10,000 human mesenchymal stem cells in 12-hour intervals and substrate stiffness-dependent synthesis by SKBR3 cells. Additionally, the approach supported osteoarthritis drug screening by identifying compounds that mitigated inflammation-induced ECM degradation. Conclusion Compared to traditional biochemical or histological assays, the click chemistry-based technique provides higher sensitivity, reduced sample requirements, and improved temporal resolution for quantifying ECM turnover. Its versatility enables broad application in tissue engineering, regenerative medicine, disease modeling, and high-throughput drug evaluation.

HieraBoost-Q: interpretable karst discharge prediction from multi-site electrical conductivity with SHAP-based mechanism insights - Yinxia Zhu; Jie Niu; Qingmin Zhu; Fen Huang; Han Qiu; Dongdong Liu; Pan Wu; Bill X. Hu (Journal of Hydrology, 2026)

Mechanistic insights into polystyrene micro/nanoplastics-facilitated cadmium trophic transfer and aggravated toxicity along a lettuce-snail terrestrial food chain - Fuyu Guo; Bo Xu; Rui Zhang; Yan Chang; Tingting Chu; Meng Zhu; Fengxiang X. Han; Ruyi Yang (Environmental Pollution, 2026)

DFODE-Kit: Deep learning package for solving flame chemical kinetics with high-dimensional stiff ordinary differential equations - Han Li; Ke Xiao; Yangchen Xu; Haoze Zhang; Zhenyi Chen; Runze Mao; Zhi X. Chen (Computer Physics Communications, 2026)

Impact of age and rurality on colorectal cancer outcomes in the United States - Caitlyn Grunert; Meng-Han Tsai; Charles R. Rogers; Sydney Howard; Rachel Hogg-Graham; Courtney Martin; Darwin Conwell; Adetunji T. Toriola; Avinash Bhakta; Justin X. Moore (Cancer Causes & Control, 2026)
Background While overall colorectal cancer (CRC) rates have declined in the United States (U.S.), early-onset CRC (EO-CRC), diagnosed before age 50, has increased. Rural U.S. residents face higher CRC incidence than non-rural counterparts. We aimed to examine the relationship between age at diagnosis and EO-CRC outcomes and whether rurality modify these associations. Methods We analyzed data from 835,907 patients aged 20–79 years in the 2006–2020 SEER Program. Rurality was defined using U.S. Department of Agriculture Rural–Urban Commuting Area (RUCA) codes. Multivariable logistic regression models were used to examine associations between age, rurality, and late-stage CRC diagnosis. Competing-risk regression models were applied to evaluate CRC-specific mortality, accounting for non–CRC deaths. Patients aged 50–59 years residing in non-rural areas served as the reference group for joint age–rurality analyses. All models adjusted for demographic, socioeconomic, clinical, and treatment factors. Results Patients aged 30–39 (aOR: 1.49, 95% CI: 1.44–1.54) and 40–49 (aOR: 1.43, 95% CI: 1.40–1.46) had significantly higher odds of late-stage CRC compared with those aged 50–59, with the strongest associations observed among non-rural patients aged 30–39 (aOR: 1.52, 95% CI: 1.46–1.58). In competing-risk models, rural patients were at higher CRC-specific mortality across all age groups, with relative hazard increases ranging from 8% in older adults (70-79) to 21% in younger adults (20-29) compared with their non-rural counterparts. Conclusion Adults aged 30–49 had higher odds of late-stage CRC than those 50–59, especially in non-rural areas. Rural residence was associated with higher CRC-specific mortality across all ages. Overall, age more strongly predicted late-stage diagnosis, while rurality more strongly predicted mortality. Earlier detection and improved clinical awareness in younger adults may reduce advanced-stage disease and CRC deaths.

Impacts of climate and land-use change on ecosystem services in the agro-pastoral ecotone of western Liaoning - Y. Li; D. Ye; X. Han; S. Xia; J. Jin; X. Jiang; L. Lv (International Journal of Environmental Science and Technology, 2026)

The mechanism and performance of new CoFe2O4/MoS2/MIL-101(Fe) activated peroxymonosulfate for efficient degradation of tetracycline - C. Zhang; X. Hou; J. Wei; K. He; X. Han; C. Wang (International Journal of Environmental Science and Technology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Optimization strategies for cultural landscape recreational safety patterns to mitigate urban heat risks - Y. Mao; H. Han; X. Meng; Y. Wan (International Journal of Environmental Science and Technology, 2026)

Cumulative environmental exposures adversely impact social behaviour and are associated with dysregulation of genes and proteins involved in epigenetic, ribosomal, and immune regulation in male mice - Morgan C. Bucknor; Brooke A. Keating; Velda X. Han; Brian S. Gloss; Pinki Dey; Nader Aryamanesh; Lee L. Marshall; Mark E. Graham; Ruwani Dissanayake; Xianzhong Lau; Shrujna Patel; Stela P. Petkova; et al. (Inflammation Research, 2026)
Objective This study investigated how cumulative environmental exposures influence offspring behaviour and inflammation-related molecular signatures in the brain and peripheral immune system. Methods A novel "triple-hit" mouse model was developed using C57Bl/6JAusB mice (N = 70), combining preconceptual social stress, antenatal high-fat diet, and a postnatal immune challenge (poly(I:C), 10 mg/kg). At 12 weeks, offspring underwent behavioural tests relevant to neurodevelopmental disorders (NDDs), including the Elevated Plus Maze, 3-Chamber Social Preference, Self-Grooming, and Marble Burying. A composite NDD-risk index was calculated. Single-cell RNA sequencing (scRNA-seq) and bulk proteomics were performed on male triple-hit offspring to identify differentially expressed genes and proteins associated with inflammatory pathways. Results Male triple-hit offspring showed elevated NDD-related behavioural risk and social deficits, not observed in females. scRNA-seq revealed altered inflammatory and ribosomal pathways in brain glia and peripheral immune cells. Proteomic analysis showed decreased abundance of proteins involved in inflammation, translation, chromatin remodelling, and synaptic function in both brain and blood. Conclusion Combined environmental stressors may drive male-specific behavioural and inflammatory changes relevant to NDDs. The identification of overlapping inflammatory signatures in brain and peripheral immune cells supports a role for shared immune mechanisms in brain–immune axis dysfunction. However, these pathway-level findings should be interpreted as preliminary hypotheses and warrant independent validation to confirm their mechanistic significance.

Cadmium immobilization and selenium mobilization by Citrobacter freundii in soil-rice system: a trade-off between remediation efficacy and soil microbial community integrity - Fuyu GUO; Tianao YU; Rui ZHANG; Tingting CHU; Meng ZHU; Shuting ZAN; Fengxiang X. HAN; Ruyi YANG (Pedosphere, 2026)

Root exudates drive metabolic remodeling of microbial and resistance to facilitate sulfonamide biodegradation in karst soil-carbonate rock interface - Yunping Zhao; Hui Mu; Bill X. Hu; Chuanshun Zhi; Hui Wang; Linxian Huang; Fen Huang; Kai Han (Journal of Hazardous Materials, 2026)

Analysis of the evolutionary patterns and drivers of Capturability of Atmospheric Water (CAW) on the Qinghai-Tibet Plateau - Hou-Liang Lu; Han Zhou; Hui-Min Zuo; Yu-Fei Jiao; Bill X. Hu (Atmospheric Research, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Exopolysaccharides from Rhizobium tropici improve flooding tolerance of Zea mays seedlings: Insights from a controlled pot study - Liang Xiao; Xinyun Xie; Steve L. Larson; John H. Ballard; Qinku Zhang; Jing Nie; Huimin Zhang; Guodong Yuan; Fengxiang X. Han (Plant and Soil, 2025)

The development of the thermal internal boundary layer and its impact on ozone vertical distribution - Z.S. Han; H.N. Liu; X. Shao; N. Zhang (Atmospheric Environment, 2025)

S30-01 Answering questions from the audience from the publisher perspective together with her fellow publisher attending the meeting Jagna Gent-Aalén - X. Han (Toxicology Letters, 2025)

Detailed simulation of RP-3 kerosene turbulent combustion using reduced chemical mechanisms - Han Li; Ke Xiao; Yifan Xu; Wenhao Yuan; Fei Qi; Zhi X. Chen (Fuel, 2025)

DeepFlame 2.0: A new version for fully GPU-native machine learning accelerated reacting flow simulations under low-Mach conditions - Runze Mao; Xinyu Dong; Xuan Bai; Ziheng Wu; Guanlin Dang; Han Li; Zhi X. Chen (Computer Physics Communications, 2025)

Exopolysaccharides from Rhizobium tropici mitigate Al phytotoxicity in Triticum aestivum - Huimin Zhang; Xinyun Xie; Steve L. Larson; John H. Ballard; Kauri A. Runge; Yan Meng; Subrata Chandra Roy; Saiful M. Islam; Fengxiang X. Han (Plant and Soil, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Positive cooperativity in synergistic activation of Wnt proteins - Clemence Bonnet; Christiana S. Han; Sophie X. Deng; Jie J. Zheng (Molecular Biology Reports, 2024)
Background Wnt proteins are crucial for embryonic development, stem cell growth, and tissue regeneration. Wnt signaling pathway is activated when Wnt proteins bind to cell membrane receptors. Methods and results We employed a luciferase reporter assay in HEK293STF cells to measure Wnt protein-induced signaling. We observed that Wnt3a uniquely promotes the Wnt/β-catenin pathway through positive cooperativity. Additionally, MFH-ND, a molecular mimic of Wnt ligands, markedly increased Wnt3a-induced signaling in a dose-responsive manner. This suggests that various Wnt ligands can synergistically enhance Wnt pathway activation. Conclusions The study suggests the likelihood of various Wnt ligands coexisting in a single signalosome on the cell membrane, providing new insights into the complexities of Wnt signaling mechanisms.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

The impact of marital status on tumor aggressiveness, treatment, and screening among black and white men diagnosed with prostate cancer - Saira Khan; Lindsay Fuzzell; Marvin Langston; Yunan Han; Justin X. Moore; Keon Gilbert; Siobhan Sutcliffe; Jeannette T. Bensen; James L. Mohler; Elizabeth T.H. Fontham; Lixin Song; Marquita W. Lewis-Thames (Cancer Causes & Control, 2024)

Effectiveness and potential mechanism of hydrothermal modification of attapulgite for cadmium passivation in soil - G. Ma; J. Ren; L. Tao; X. Han; C. Liao; Y. Zhou; J. Ding; Y. Zhou; K. Bi (International Journal of Environmental Science and Technology, 2024)

Early-Life Social Determinants of SCA6 Age at Onset, Severity, and Progression - Tiffany X. Chen; Hannah L. Casey; Chi-Ying R. Lin; Theresa A. Boyle; Jeremy D. Schmahmann; Gilbert J. L’Italien; Sheng-Han Kuo; Christopher M. Gomez (The Cerebellum, 2024)
SCA6 patients with the same size CAG repeat allele can vary significantly in age at onset (AAO) and clinical progression. The specific external factors affecting SCA6 have yet to be investigated. We assessed the effect of early life events on AAO, severity, and progression in SCA6 patients using a social determinant of health approach. We performed a survey of biological and social factors in SCA6 patients enrolled in the SCA6 Network at the University of Chicago. AAO of ataxia symptoms and patient-reported outcome measure (PROM) of ataxia were used as primary outcome measures. Least absolute shrinkage and selection operation (LASSO) regressions were used to identify which early life factors are predictive of SCA6 AAO, severity, and progression. Multiple linear regression models were then used to assess the degree to which these determinants influence SCA6 health outcomes. A total of 105 participants with genetically confirmed SCA6 completed the assessments. SCA6 participants with maternal difficulty during pregnancy, active participation in school sports, and/or longer CAG repeats were determined to have earlier AAO. We found a 13.44-year earlier AAO for those with maternal difficulty in pregnancy than those without ( p = 0.008) and a 12.31-year earlier AAO for those active in school sports than those who were not ( p < 0.001). Higher education attainment was associated with decreased SCA6 severity and slower progression. Early life biological and social factors can have a strong influence on the SCA6 disease course, indicating that non-genetic factors can contribute significantly to SCA6 health outcomes.

Radiocarbon integrity of dissolved inorganic carbon (DIC) samples stored in plastic and glass bottles: implications for reliable groundwater age dating - David X. Soto; Luis J. Araguás-Araguás; Liang-Feng Han; Leonard I. Wassenaar (Isotopes in Environmental and Health Studies, 2024)

Review of risk assessment for navigational safety and supported decisions in arctic waters - X. Yang; Z.Y. Lin; W.J. Zhang; S. Xu; M.Y. Zhang; Z.D. Wu; B. Han (Ocean & Coastal Management, 2024)

A bibliometric analysis of the toxicity research of carbon nanomaterials - M. Han; Y. Lei; F. X. Yang; H. F. Sun (International Journal of Environmental Science and Technology, 2024)

Comparison of PM2.5 components and secondary formation during the heavily polluted period of two megacities in China - Z. Ran; X. Wang; X. Yin; Y. Liu; M. Han; Y. Cheng; J. Han; T. Jin (International Journal of Environmental Science and Technology, 2024)

Interaction of exopolysaccharide with clay minerals and their effects on U(VI) adsorption - Huimin Zhang; Steve Larson; John Ballard; Jing Nie; Qiqi Zhang; Joseph A. Kazery; Shaloam Dasari; Nihar Pradhan; Qilin Dai; Olanrewaju M. Olafuyi; Xianchun Zhu; Youhua Ma; et al. (Journal of Soils and Sediments, 2023)

Evaluation of Agricultural Non-point Source Pollution: a Review - Mei Luo; Xiaoxiao Liu; Nebiyou Legesse; Ying Liu; Sheng Wu; Fengxiang X. Han; Youhua Ma (Water, Air, & Soil Pollution, 2023)

Functional traits explain waterbirds' host status, subtype richness, and community‐level infection risk for avian influenza - Shenglai Yin; Ning Li; Wenjie Xu; Daniel J. Becker; Willem F. de Boer; Chi Xu; Taej Mundkur; Nicholas M. Fountain‐Jones; Chunlin Li; Guan‐zhu Han; Qiang Wu; Diann J. Prosser; et al. (Ecology Letters, 2023)
Species functional traits can influence pathogen transmission processes, and consequently affect species' host status, pathogen diversity, and community‐level infection risk. We here investigated, for 143 European waterbird species, effects of functional traits on host status and pathogen diversity (subtype richness) for avian influenza virus at species level. We then explored the association between functional diversity and HPAI H5Nx occurrence at the community level for 2016/17 and 2021/22 epidemics in Europe. We found that both host status and subtype richness were shaped by several traits, such as diet guild and dispersal ability, and that the community‐weighted means of these traits were also correlated with community‐level risk of H5Nx occurrence. Moreover, functional divergence was negatively associated with H5Nx occurrence, indicating that functional diversity can reduce infection risk. Our findings highlight the value of integrating trait‐based ecology into the framework of diversity–disease relationship, and provide new insights for HPAI prediction and prevention.

P09-32: The mechanism of PGE2 on apoptosis of rat ovarian granulosa cells induced by MEHP - S. Ren; X. Han; X. Li; X. Li; L. Ye (Toxicology Letters, 2023)

Efficient denitrification by a salt-tolerant aerobic compound bacteria agent AHM M3: optimizing composition and reduction conditions - H. Ma; Y. Liu; X. Mu; J. Song; X. Su; Y. Wu; R. Han (International Journal of Environmental Science and Technology, 2023)

Paleocurrent and paleowind direction reconstruction research progress and perspectives: a review - F. Y. Zhao; C. L. Hu; C. C. Han; Y. Q. Dong; Q. X. Yuan (Australian Journal of Earth Sciences, 2023)

Rebound effect of carbon emissions of new energy vehicle consumption: a case study of Beijing - J. Zhou; W. Fang; X. Han; Q. Sun; D. Liu; S. Liu (International Journal of Environmental Science and Technology, 2023)

Effects of aluminum ion on particle sizes and surface charges of exopolysaccharides from Rhizobium tropici and pH effects - Steve L. Larson; John H. Ballard; Kauri A. Runge; Huimin Zhang; Benjamin R. Breland; Zachary H. Nick; Ethan Tyler Vroman; Charles A. Weiss; Fengxiang X. Han (Rhizosphere, 2023)

Pulmonary vasculitis in COVID-19: findings in the mouse model and comparison to other respiratory viral infections - A. Kipar; J.J. Clark; X. Han; E. Bentley; J.P. Stewart (Journal of Comparative Pathology, 2023)

Identification for discharged characteristics of fine particulate matter from coke chemical industry in northern China - J. Luo; X. Feng; H. Han; N. Wang (International Journal of Environmental Science and Technology, 2023)

Elastoplastic Modelling of Porous Limestones with Porosity Dependency - B. Han; Q. M. Gong; X. L. Du; Y. Gao; W. Q. Shen; S. Lin (Rock Mechanics and Rock Engineering, 2022)

A comparative study on adsorption of cadmium and lead by hydrochars and biochars derived from rice husk and Zizania latifolia straw - Xinyuan Zhang; Zixiang Gao; Xiaoping Fan; Li Tan; Yishun Jiang; Wanning Zheng; Fengxiang X. Han; Yongchao Liang (Environmental Science and Pollution Research, 2022)

A New Berberine Preparation Protects Pancreatic Islet Cells from Apoptosis Mediated by Inhibition of Phospholipase A2/p38 MAPK Pathway - X. J. Bi; Y. Q. Lv; X. H. Yang; Y. Ge; H. Han; J. S. Feng; M. Zhang; L. Chen; M. Z. Xu; F. Y. Guan (Bulletin of Experimental Biology and Medicine, 2022)

An analysis of coupling coordination relationship between regional economy and transportation: empirical evidence from China - Qiang Du; Xinqi Wang; Yi Li; Patrick X. W. Zou; Xiao Han; Meng Meng (Environmental Science and Pollution Research, 2022)

Delayed rFGF21 Administration Improves Cerebrovascular Remodeling and White Matter Repair After Focal Stroke in Diabetic Mice - Yinghua Jiang; Jinrui Han; Yadan Li; Yinga Wu; Ning Liu; Samuel X. Shi; Li Lin; Jing Yuan; Shusheng Wang; Ming-Ming Ning; Aaron S. Dumont; Xiaoying Wang (Translational Stroke Research, 2022)

Identification and Verification of the Ability of Cdk5 to Phosphorylate Deubiquitinating Enzyme BRCC3 In Vitro - C. H. Zhang; K. Qin; S. L. Tian; Y. Han; S. Y. Xu; X. Y. Shao (Bulletin of Experimental Biology and Medicine, 2022)

Uranium Adsorption on Three Nanohydroxyapatites Under Various Biogeochemical Conditions - Precious Cooper; Jing Nie; Steven L. Larson; John H. Ballard; Heather M. Knotek-Smith; Ahmet Celik; Shaloam Dasari; Xianchun Zhu; Fengxiang X. Han (Water, Air, & Soil Pollution, 2021)

Synthesis of a novel ZnFe2O4/porous biochar magnetic composite for Th(IV) adsorption in aqueous solutions - W. D. Wang; Y. X. Cui; L. K. Zhang; Y. M. Li; P. Sun; J. H. Han (International Journal of Environmental Science and Technology, 2021)

Correction to: Identification and molecular characterization of tea‑oil camellia‑associated totivirus 1 - Z.-Y. Zhang; H. Huang; X. X. Han; R. Li; L.-P. Wu; L. Wu (Archives of Virology, 2021)

Identification and molecular characterization of tea-oil camellia-associated totivirus 1 - Z.-Y. Zhang; H. Huang; X. X. Han; R. Li; L.-P. Wu; L. Wu (Archives of Virology, 2021)

Microbially Induced Carbonate Precipitation Techniques for the Remediation of Heavy Metal and Trace Element–Polluted Soils and Water - Xue Chen; Dan Zhang; Steven L. Larson; John H. Ballard; Heather M. Knotek-Smith; Jing Nie; Nan Hu; Dexin Ding; Fengxiang X. Han (Water, Air, & Soil Pollution, 2021)

Kinetic and Thermodynamic Features of Pb(II) Removal From Aqueous Solution by Leonardite-Derived Humic Acid - Fande Meng; Yuwei Zhang; Yongbing Cai; Guodong Yuan; Feng X. Han (Water, Air, & Soil Pollution, 2021)

Pseudomonas koreensis promotes tomato growth and shows potential to induce stress tolerance via auxin and polyphenol‐related pathways - Q. Guo; Y. Sun; M. Shi; X. Han; Y. Jing; Y. Li; H. Li; H. Lai (Plant and Soil, 2021)

Application of two-level design method on subway tunnel crossing active fault: a case study on Urumqi subway tunnel intersected by reverse fault dislocation - S. An; L. J. Tao; X. C. Han; Y. Zhang (Bulletin of Engineering Geology and the Environment, 2021)

Gga-miR-181a modulates ANP32A expression and inhibits MDCC-MSB-1 cell - X. Li; C. Zhao; B. Han; L. Qu; C. Liu; N. Yang; L. Lian (In Vitro Cellular & Developmental Biology - Animal, 2021)

The Efficacy and Safety of Transcranial Direct Current Stimulation for Cerebellar Ataxia: a Systematic Review and Meta-Analysis - Tiffany X. Chen; Chen-Ya Yang; Gloria Willson; Chih-Chun Lin; Sheng-Han Kuo (The Cerebellum, 2021)

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Carbon accumulation in agroforestry systems is affected by tree species diversity, age and regional climate: A global meta‐analysis - Zilong Ma; Han Y. H. Chen; Edward W. Bork; Cameron N. Carlyle; Scott X. Chang (Global Ecology and Biogeography, 2020)
Aim Agroforestry is a globally practised system of land use for achieving greater and more diverse biomass production, but it has other ecological benefits, such as mitigation of climate change. Despite this, long‐term carbon (C) accumulation in different components of agroforestry systems, the drivers for C accumulation and the linkages between tree biomass and soil C stocks remain unclear. Location Global. Time period From 1989 to 2019. Major taxa studied Trees. Methods Here, we report on a global meta‐analysis based on 141 studies to identify patterns of C accumulation in tree‐based agroforestry systems compared with sole cropland and pasture. Results We found that agroforestry systems had, on average, 46.1 Mg/ha (95% confidence interval, 36.4–55.8 Mg/ha) more C in tree biomass compared with sole cropland‐ or pasture‐based land uses without trees. Furthermore, agroforestry systems with multiple tree species contained greater biomass C stocks and accumulated biomass C faster than systems with a single tree species. The effect of agroforestry practices on soil C stock increased with tree age, although such increases varied among climatic zones. Agroforestry systems in tropical zones had the ability to increase soil C to peak levels quickly, whereas soil C in temperate zones increased at a slower rate but peaked at a greater overall soil C level. Our structural equation model did not detect a direct linkage between biomass C and changes in total soil C stock in agroforestry systems. Main conclusions Our results demonstrate that planting multiple tree species in agroforestry systems is an important strategy to increase biomass C sequestration, with regional climate affecting the temporal change of soil C in response to agroforestry practices.

Genetic and antigenic characterization of influenza A/H5N1 viruses isolated from patients in Indonesia, 2008–2015 - Hana A. Pawestri; Arie A. Nugraha; Alvin X. Han; Eka Pratiwi; Edyth Parker; Mathilde Richard; Stefan van der Vliet; Ron A. M. Fouchier; David H. Muljono; Menno D. de Jong; Vivi Setiawaty; Dirk Eggink (Virus Genes, 2020)

The effect of enrichment media on the stimulation of native ureolytic bacteria in calcareous sand - Y.-J. Wang; X.-L. Han; N.-J. Jiang; J. Wang; J. Feng (International Journal of Environmental Science and Technology, 2020)

Cattle urine and dung additions differently affect nitrification pathways and greenhouse gas emission in a grassland soil - Qian Wu; Jin-Hyeob Kwak; Scott X. Chang; Guodong Han; Xiaoqiang Gong (Biology and Fertility of Soils, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

A high production of flavonoids and anthraquinones via adventitious root culture of Oplopanax elatus and evaluating antioxidant activity - L. Han; X. C. Piao; J. Jiang; X. L. Jiang; C. R. Yin; M. L. Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Identification of phosphorylated proteins in response to salt stress in wheat embryo and endosperm during seed germination - X. Luo; C. Han; X. Deng; D. Zhu; Y. Liu; Y. Yan (Cereal Research Communications, 2019)

High frequency and diversity of parechovirus A in a cohort of Malawian children - Lieke Brouwer; Eveliina Karelehto; Alvin X. Han; Xiomara V. Thomas; Andrea H. L. Bruning; Job C. J. Calis; Michaël Boele van Hensbroek; Brenda M. Westerhuis; Darsha Amarthalingam; Sylvie M. Koekkoek; Sjoerd P. H. Rebers; Kamija S. Phiri; et al. (Archives of Virology, 2019)

Detecting hydrological consistency between soil moisture and precipitation and changes of soil moisture in summer over the Tibetan Plateau - X. Meng; R. Li; L. Luan; S. Lyu; T. Zhang; Y. Ao; B. Han; L. Zhao; Y. Ma (Climate Dynamics, 2018)

Influences of U Sources and Forms on Its Bioaccumulation in Indian Mustard and Sunflower - Fande Meng; Decheng Jin; Kai Guo; Steven L. Larson; John H. Ballard; Liangmei Chen; Zikri Arslan; Guodong Yuan; Jeremy R. White; Lixiang Zhou; Youhua Ma; Charles A. Waggoner; et al. (Water, Air, & Soil Pollution, 2018)

Optimization of culture medium components and culture period for production of adventitious roots of Echinacea pallida (Nutt.) Nutt - Y. Gao; C. H. Wu; X. C. Piao; L. Han; R. Gao; M. L. Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Linking muscle metabolism and functional variation to field swimming performance in bluegill sunfish (Lepomis macrochirus) - David J. Ellerby; Shauna Cyr; Angela X. Han; Mika Lin; Lloyd A. Trueblood (Journal of Comparative Physiology B, 2018)

Novel Magnetic Nanocarbon and Its Adsorption of Hg and Pb from Water - Kai Guo; Steven L. Larson; John H. Ballard; Zikri Arslan; Rong Zhang; Yong Ran; Yi Su; Fengxiang X. Han (Water, Air, & Soil Pollution, 2018)

Visco-elastic–Plastic Creep Constitutive Relation of Tunnels in Soft Schist - Y. Y. Zuo; L. Han; H. Hu; S. Y. Luo; Y. Zhang; X. M. Chen (Geotechnical and Geological Engineering, 2018)

Design, synthesis, antitumor evaluation, 3D-QSAR and molecular docking studies of novel 4-aminoacridone compounds - Lin Tian; Chang J. Feng; Tong X. Li; Zhao Li; Wei H. Yang; Xiang E. Han (Medicinal Chemistry Research, 2017)

Removal of Cr(VI) and phenol coupled with the reduction of sulfate by sulfate-reducing bacteria sludge - X. Han; T.-X. Zhou; S.-W. Xu; Y. Li; Y.-F. Wang; Y. Liu (International Journal of Environmental Science and Technology, 2017)

Soil Organic Carbon Dynamics Responses to Soil Fertility in the Agricultural Regions of China - D. L. Han; X. P. Zhu; H. T. Jia; P. J. Yu (Agricultural Research, 2017)

Study on the application of an activator for steel slag powder–cement in muddy soil - Y. K. Wu; X. S. Hu; R. Hu; T. Han; J. L. Yu (European Journal of Environmental and Civil Engineering, 2017)

Response of plant functional traits to species origin and adaptive reproduction in weeds - J. H. Liu; X. H. Yong; Q. Han; A. Ali; Y. J. Wang (Plant Biosystems, 2017)

Sequence variants of the LCORL gene and its association with growth and carcass traits in Qinchuan cattle in China - Y. J. HAN; Y. CHEN; Y. LIU; X. L. LIU (Journal of Genetics, 2017)

Trace Elements and Heavy Metals in Asian Rice-Derived Food Products - Kai Guo; Shenita Wells; Fengxiang X. Han; Zikri Arslan; Hua Sun; Jiuquan Zhang (Water, Air, & Soil Pollution, 2017)

Structuraland antigenic analysis of a new Rhoptry Pseudokinase Gene (ROP54) in Toxoplasma gondii - Jian Zhou; Gang Lu; Lin Wang; Aihua H. Zhou; Yali L. Han; Jingjing J. Guo; Pengxia X. Song; Huaiyu Y. Zhou; Hua Cong; Ming Hou; Shenyi Y. He (Acta Parasitologica, 2017)
is defined as an obligate intracellular apicomplexan parasite and influences approximatelyone-third of the human all over the world. ROP54 protein is expressed in the rhoptry of

Effects of Operation Variables and Electro-kinetic Field on Soil Washing of Arsenic and Cesium with Potassium Phosphate - Xinyu Mao; Fengxiang X. Han; Xiaohou Shao; Zikri Arslan; Jacqueline McComb; Tingting Chang; Kai Guo; Ahmet Celik (Water, Air, & Soil Pollution, 2017)

Development of novel nanomaterials for remediation of heavy metals and radionuclides in contaminated water - Kai Guo; Fengxiang X. Han; William Kingery; Hua Sun; Jiuquan Zhang (Nanotechnology for Environmental Engineering, 2016)

Microstructure and Ultrastructure Alterations in the Pallium of Immature Mice Exposed to Cadmium - X. F. Yang; Q. G. Han; D. Y. Liu; H. T. Zhang; G. Y. Fan; J. Y. Ma; Z. L. Wang (Biological Trace Element Research, 2016)

Remediation of lead-, arsenic-, and cesium-contaminated soil using consecutive washing enhanced with electro-kinetic field - Xinyu Mao; Fengxiang X. Han; Xiaohou Shao; Zikri Arslan; Jacqueline McComb; Tingting Chang; Kai Guo; Ahmet Celik (Journal of Soils and Sediments, 2016)

The effects of petroleum-contaminated soil on photosynthesis of Amorpha fruticosa seedlings - G. Han; B. X. Cui; X. X. Zhang; K. R. Li (International Journal of Environmental Science and Technology, 2016)

The distribution and elevated solubility of lead, arsenic and cesium in contaminated paddy soil enhanced with the electrokinetic field - X. Mao; F. X. Han; X. Shao; K. Guo; J. McComb; S. Njemanze; Z. Arslan; Z. Zhang (International Journal of Environmental Science and Technology, 2016)

Binding, fractionation, and distribution of Cs, Co, and Sr in a US coastal soil under saturated and field capacity moisture regimes - Leondra S. Lawson; Jacqueline Q. McComb; Ruipong Dong; Fengxiang X. Han; Christian Roger; Zikri Arslan; Hongtao Yu (Journal of Soils and Sediments, 2016)

Stress-Induced Increases in Levels of Caspases in the Prefrontal Cortex in a Rat Model of PTSD - J. H. Zhang; M. Li; F. Han; Yu X. Shi (Neurophysiology, 2016)

Roles of the Fibrous Superficial Zone in the Mechanical Behavior of TMJ Condylar Cartilage - Leonardo Ruggiero; Brandon K. Zimmerman; Miri Park; Lin Han; Liyun Wang; David L. Burris; X. Lucas Lu (Annals of Biomedical Engineering, 2015)

QTL mapping of adult-plant resistance to stripe rust in wheat line P9897 - X. L. Zhou; D. J. Han; X. M. Chen; J. M. Mu; W. B. Xue; Q. D. Zeng; Q. L. Wang; L. L. Huang; Z. S. Kang (Euphytica, 2015)

Identification of QTL for adult plant resistance to stripe rust in Chinese wheat landrace Caoxuan 5 - X. L. Zhou; Y. Zhang; Q. D. Zeng; X. M. Chen; D. J. Han; L. L. Huang; Z. S. Kang (Euphytica, 2015)

Indirect interactions among tropical tree species through shared rodent seed predators: a novel mechanism of tree species coexistence - Carol X. Garzon‐Lopez; Liliana Ballesteros‐Mejia; Alejandro Ordoñez; Stephanie A. Bohlman; Han Olff; Patrick A. Jansen (Ecology Letters, 2015)
The coexistence of numerous tree species in tropical forests is commonly explained by negative dependence of recruitment on the conspecific seed and tree density due to specialist natural enemies that attack seeds and seedlings (‘Janzen–Connell’ effects). Less known is whether guilds of shared seed predators can induce a negative dependence of recruitment on the density of different species of the same plant functional group. We studied 54 plots in tropical forest on Barro Colorado Island, Panama, with contrasting mature tree densities of three coexisting large seeded tree species with shared seed predators. Levels of seed predation were far better explained by incorporating seed densities of all three focal species than by conspecific seed density alone. Both positive and negative density dependencies were observed for different species combinations. Thus, indirect interactions via shared seed predators can either promote or reduce the coexistence of different plant functional groups in tropical forest.

The potential and electric field in the cochlear outer hair cell membrane - Ben Harland; Wen-han Lee; William E. Brownell; Sean X. Sun; Alexander A. Spector (Medical & Biological Engineering & Computing, 2015)

Application of a high-surface-area schwertmannite in the removal of arsenate and arsenite - J. Song; S.-Y. Jia; H.-T. Ren; S.-H. Wu; X. Han (International Journal of Environmental Science and Technology, 2015)

Sensitivity of Alternaria solani to boscalid and control of boscalid resistance with commonly-used fungicides in Shanxi, China - X. J. Shi; L. Ren; Y. Q. Song; J. C. Han; H. P. Liu; Y. J. Zhang (Australasian Plant Pathology, 2015)

Soil and plant nitrogen pools in paddy and upland ecosystems have contrasting δ15N - Sang-Sun Lim; Jin-Hyeob Kwak; Kwang-Seung Lee; Scott X. Chang; Kwang-Sik Yoon; Han-Yong Kim; Woo-Jung Choi (Biology and Fertility of Soils, 2015)

Rapid Screening of Heavy Metals and Trace Elements in Environmental Samples Using Portable X-Ray Fluorescence Spectrometer, A Comparative Study - Jacqueline Q. McComb; Christian Rogers; Fengxiang X. Han; Paul B. Tchounwou (Water, Air, & Soil Pollution, 2014)

Characterization and molecular mapping of stripe rust resistance gene Yr61 in winter wheat cultivar Pindong 34 - X. L. Zhou; D. J. Han; X. M. Chen; H. L. Gou; S. J. Guo; L. Rong; Q. L. Wang; L. L. Huang; Z. S. Kang (Theoretical and Applied Genetics, 2014)

Effects of Transduction of the bcl-2 Gene and of Nerve Growth Factor on Apoptosis of Cultured PC12 Cells - G. Han; W. Wei; X. Zhang; Zh. Lai; Ch. Chen (Neurophysiology, 2014)

Erratum to: Rapid Determination of Mercury in Contaminated Soil and Plant Samples Using Portable Mercury Direct Analyzer Without Sample Preparation, a Comparative Study - John G. Kelly; Fengxiang X. Han; Yi Su; Yunjun Xia; Valerie Philips; Zhiqi Shi; David L. Monts; Sergio T. Pichardo; Kang Xia (Water, Air, & Soil Pollution, 2014)

Adsorption of anionic dye on magnesium hydroxide-coated pyrolytic bio-char and reuse by microwave irradiation - X. N. Zhang; G. Y. Mao; Y. B. Jiao; Y. Shang; R. P. Han (International Journal of Environmental Science and Technology, 2014)

Family-based association study of ZNF533, DOCK4 and IMMP2L gene polymorphisms linked to autism in a northeastern Chinese Han population - Shuang Liang; Xue-lai Wang; Ming-yang Zou; Han Wang; Xue Zhou; Cai-hong Sun; Wei Xia; Li-jie Wu; Takashi X. Fujisawa; Akemi Tomoda (Journal of Zhejiang University-SCIENCE B, 2014)

Molecular mapping of a stripe rust resistance gene in wheat cultivar Wuhan 2 - X. L. Zhou; D. J. Han; H. L. Gou; Q. L. Wang; Q. D. Zeng; F. P. Yuan; G. M. Zhan; L. L. Huang; Z. S. Kang (Euphytica, 2014)
Stripe rust (or yellow rust), caused by Puccinia striiformis f. sp. tritici , is one of the most destructive diseases of wheat worldwide. Growing resistant cultivars is the best approach to control the disease. To identify and map genes for stripe rust resistance in wheat cultivar ‘Wuhan 2', an F 2 population was developed from a cross between the cultivar and susceptible cultivar Mingxian 169. The parents, 179 F 2 plants and their derived F 2:3 lines were evaluated for responses to Chinese races CYR30 and CYR31 of the pathogen in a greenhouse. A recessive gene for resistance was identified. DNA bulked segregant analysis was applied and resistance gene analog polymorphism (RGAP) and simple sequence repeat (SSR) techniques were used to identify molecular markers linked to the resistance gene. A genetic map consisting of five RGAP and six SSR markers was constructed. The recessive gene, designated Yrwh2 , was located on the short arm of chromosome 3B and flanked by SSR markers Xwmc540 and Xgwm566 at 5.9 and 10.0 cM, respectively. The chromosomal location of the resistance gene and its close marker suggest that the locus is different from previously reported stripe rust resistance genes Yr30 , QYr.ucw - 3BS , Yrns - B1 , YrRub and QYrex.wgp - 3BL previously mapped to chromosome 3B. Yrwh2 and its closely linked markers are potentially useful for developing stripe rust resistance wheat cultivars if used in combination with other genes.

Applications of capillary electrophoresis for rapidly separating and characterizing water-soluble proteins of wheat grains - C. Han; Z. Yu; S. Feng; D. Lv; X. Yan; G. Chen; X. Li; W. Ma; Y. Yan (Cereal Research Communications, 2013)

Challenge of weed risk assessment (WRA) for ecological restoration in China: The case of Rhus typhina L. and the new officially released weed risk assessment system - G. M. Wang; J. C. Yang; C. D. Jiang; G. M. Jiang; J. B. Yu; H. B. Shao; G. X. Han; Y. J. Gao (Plant Biosystems, 2013)

The C‐terminal cysteine of turbot Scophthalmus maximus translationally controlled tumour protein plays a key role in antioxidation and growth‐promoting functions - Z.‐X. Zhang; D.‐Y. Geng; Q. Han; S.‐D. Liang; H.‐R. Guo (Journal of Fish Biology, 2013)
The translationally controlled tumour protein (TCTP) of turbot Scophthalmus maximus ( SmTCTP ) contains only one cysteine (Cys 170 ) at the C‐terminal end. The biological role of this C‐terminal Cys 170 in the antioxidation and growth‐promoting functions of SmTCTP was examined by site‐directed mutation of C170A (Cys 170 →Ala 170 ). It was found that C170A mutation not only obviously decreased the antioxidation capacity of the mutant‐ smtctp ‐transformed bacteria exposed to 0·22 mM hydrogen peroxide, but also significantly interrupted the normal growth and survival of the mutant‐ smtctp ‐transformed bacteria and flounder Paralichthys olivaceus gill ( FG ) cells, indicating a key role played by Cys 170 in the antioxidation and growth‐promoting functions of SmTCTP . This study also suggested that the self‐dimerization or dimerization with other interacting proteins is critical to the growth‐promoting function of SmTCTP .

Numerical Analysis of Seismic Dynamic Response of Saturated Porous Seabed Around a Buried Pipeline - X. L. Zhang; Y. Han (Marine Georesources & Geotechnology, 2013)

Evaluation of organic contamination in urban groundwater surrounding a municipal landfill, Zhoukou, China - D. M. Han; X. X. Tong; M. G. Jin; Emily Hepburn; C. S. Tong; X. F. Song (Environmental Monitoring and Assessment, 2013)

Study of chloropropanols in soy sauce by gas chromatography-triple quadrupole mass spectrometry with coupled column separation without derivatisation - X.-M. Xu; H.-W. Wu; H.-L. He; B.-F. Huang; J.-L. Han; Y.-P. Ren (Food Additives & Contaminants: Part A, 2013)

Foliar chemistry and tree ring δ13C of Pinus densiflora in relation to tree growth along a soil pH gradient - Hung Dinh Viet; Jin-Hyeob Kwak; Kwang-Seung Lee; Sang-Sun Lim; Miwa Matsushima; Scott X. Chang; Kye-Han Lee; Woo-Jung Choi (Plant and Soil, 2013)

Effect of cholesterol on lipogenesis and VLDL–TG assembly and secretion in goose primary hepatocytes - C. C. Han; J. W. Wang; Z. X. Pan; H. Tang; S. X. Xiang; J. Wang; L. Li; F. Xu; S. H. Wei (Molecular and Cellular Biochemistry, 2013)

Choice of microsatellite markers for identifying homozygosity of mitotic gynogenetic diploids in Japanese flounder Paralichthys olivaceus - Y. X. Liu; H. Z. Han; Q. L. Wang; L. Jiang; S. L. Wang; X. Y. Zhang; Y. Liu; Y. F. Wang; Y. J. Liu; H. J. Liu (Journal of Fish Biology, 2013)
A set of 72 microsatellite markers distributed evenly among 24 linkage groups were selected from the published genetic linkage maps of Japanese flounder Paralichthys olivaceus . In two normal diploid full‐sib families, the test for Mendelian inheritance showed that genotypic segregation deviations were not significant at all analysed loci. To estimate microsatellite‐centromere map distances, four meiotic gynogenetic diploid lines were produced by the activation of eggs using UV irradiated sperm of red seabream Pagrus major and cold‐shock treatment to block the extrusion of the second polar body. Under the assumption of complete interference, 21 markers were located in the centromeric region, 39 in the telomeric region and the rest in the intermediate region of linkage groups. A total of 192 mitotic gynogenetic diploids from one spawn were identified by these markers. Genotype analysis showed that the number of homozygous individuals decreased as microsatellite‐centromere map distance increased on each linkage group.

Classification of Surface EMGs Using Wavelet Packet Energy Analysis and a Genetic Algorithm-Based Support Vector Machine - Y. Rong; D. Hao; X. Han; Y. Zhang; J. Zhang; Y. Zeng (Neurophysiology, 2013)

Water Maze Spatial Learning Enhances Social Recognition Ability in Aged Rats - Q. Zeng; J. Han; B. Wang; Sh. An; Y. Duan; S. Dong; J. Ma; L. Yang; X. Cao (Neurophysiology, 2012)

Specific herbivore‐induced volatiles defend plants and determine insect community composition in the field - Y. Xiao; Q. Wang; M. Erb; T. C. J. Turlings; L. Ge; L. Hu; J. Li; X. Han; T. Zhang; J. Lu; G. Zhang; Y. Lou (Ecology Letters, 2012)
In response to insect attack, plants release complex blends of volatile compounds. These volatiles serve as foraging cues for herbivores, predators and parasitoids, leading to plant‐mediated interactions within and between trophic levels. Hence, plant volatiles may be important determinants of insect community composition. To test this, we created rice lines that are impaired in the emission of two major signals, S‐ linalool and ( E )‐β‐caryophyllene. We found that inducible S‐ linalool attracted predators and parasitoids as well as chewing herbivores, but repelled the rice brown planthopper Nilaparvata lugens , a major pest. The constitutively produced ( E )‐β‐caryophyllene on the other hand attracted both parasitoids and planthoppers, resulting in an increased herbivore load. Thus, silencing either signal resulted in specific insect assemblages in the field, highlighting the importance of plant volatiles in determining insect community structures. Moreover, the results imply that the manipulation of volatile emissions in crops has great potential for the control of pest populations.

Rapid Determination of Mercury in Contaminated Soil and Plant Samples Using Portable Mercury Direct Analyzer without Sample Preparation, a Comparative Study - John G. Kelly; Fengxiang X. Han; Yi Su; Yunjun Xia; Valerie Philips; Zhiqi Shi; David L. Monts; Sergio T. Pichardo; Kang Xia (Water, Air, & Soil Pollution, 2012)

Isolation, mapping, SNP detection and association with backfat traits of the porcine CTNNBL1 and DGAT2 genes - Q. Yin; H. -W. Yang; X. -L. Han; B. Fan; B. Liu (Molecular Biology Reports, 2012)

Case report: a p.C618S RET proto-oncogene germline mutation in a large Chinese pedigree with familial medullary thyroid carcinoma - X.-P. Qi; R.-B. Ying; J.-M. Ma; W.-T. Liu; Z.-F. Du; J. Fei; C.-P. Yang; Q.-Z. Song; H.-Y. Jin; Z.-G. Chen; J.-S. Han; J.-Q. Wang; et al. (Familial Cancer, 2012)

Soil organic C, nutrients, microbial biomass, and grain yield of rice (Oryza sativa L.) after 18 years of fertilizer application to an infertile paddy soil - Meirong Lv; Zhongpei Li; Yuping Che; F. X. Han; Ming Liu (Biology and Fertility of Soils, 2011)

Potential use of δ 13C, δ 15N, N concentration, and Ca/Al of Pinus densiflora tree rings in estimating historical precipitation pH - Jin-Hyeob Kwak; Sang-Sun Lim; Scott X. Chang; Kye-Han Lee; Woo-Jung Choi (Journal of Soils and Sediments, 2011)

Health Risk Assessment of Organochlorine Contaminants in Fish from a Major Lake (Baiyangdian Lake) in North China - G. H. Dai; X. H. Liu; G. Liang; M. Z. Xu; X. Han; L. Shi (Bulletin of Environmental Contamination and Toxicology, 2011)

Determination of Imazaquin and its Metabolite by Liquid Chromatography-Quadrupole-Time of Flight Tandem Mass - H. B. Yao; G. J. Han; G. X. Liu; Y. Xie; C. H. Wang (Bulletin of Environmental Contamination and Toxicology, 2010)

Effect of paraquat on the antioxidative enzyme activities and lipid peroxidation in opium poppy (Papaver somniferum L.) - R. Zhao; P. -Y. Guo; X. -Y. Yuan; J. -Y. Wang; M. -Q. Han (Journal of Plant Diseases and Protection, 2010)

A novel single-nucleotide polymorphism of thevisfatin gene and its associations with performance traits in the chicken - R. L. Han; X. Y. Lan; L. Z. Zhang; G. Ren; Y. J. Jing; M. J. Li; B. Zhang; M. Zhao; Y. K. Guo; X. T. Kang; H. Chen (Journal of Applied Genetics, 2010)

Analysis of genetic structure and relationship among nine indigenous Chinese chicken populations by the Structure program - H. F. Li; W. Han; Y. F. Zhu; J. T. Shu; X. Y. Zhang; K. W. Chen (Journal of Genetics, 2009)

Relating Tree Ring Chemistry of Pinus densiflora to Precipitation Acidity in an Industrial Area of South Korea - Jin-Hyeob Kwak; Sang-Sun Lim; Hyun-Jung Park; Sun-Il Lee; Kye-Han Lee; Han-Yong Kim; Scott X. Chang; Sang-Mo Lee; Hee-Myong Ro; Woo-Jung Choi (Water, Air, & Soil Pollution, 2009)

Detection of Autoinducer-2 and Analysis of the Profile of luxS and pfs Transcription in Streptococcus suis Serotype 2 - X. G. Han; C. P. Lu (Current Microbiology, 2009)

Estimation of the gross primary production of an old‐growth temperate mixed forest using eddy covariance and remote sensing - J. B. Wu; X. M. Xiao; D. X. Guan; T. T. Shi; C. J. Jin; S. J. Han (International Journal of Remote Sensing, 2009)

Bioaccumulation and physiological effects of mercury in Pteris vittata and Nephrolepis exaltata - Jian Chen; Safwan Shiyab; Fengxiang X. Han; David L. Monts; Charles A. Waggoner; Zhimin Yang; Yi Su (Ecotoxicology, 2009)

Ivermectin inhibits LPS-induced production of inflammatory cytokines and improves LPS-induced survival in mice - X. Zhang; Y. Song; X. Ci; N. An; Y. Ju; H. Li; X. Wang; C. Han; J. Cui; X. Deng (Inflammation Research, 2008)

Extractability and Bioavailability of Mercury from a Mercury Sulfide Contaminated Soil in Oak Ridge, Tennessee, USA - Fengxiang X. Han; Safwan Shiyab; Jian Chen; Yi Su; David L. Monts; Charles A. Waggoner; Frank B. Matta (Water, Air, & Soil Pollution, 2008)

Inhibition of the development of collagen-induced arthritis in Wistar rats through vagus nerve suspension: a 3-month observation - P. Zhang; D. Han; T. Tang; X. Zhang; K. Dai (Inflammation Research, 2008)

Changes in Chlorophyll Fluorescence in Maize Plants with Imposed Rapid Dehydration at Different Leaf Ages - Z. Z. Xu; G. S. Zhou; Y. L. Wang; G. X. Han; Y. J. Li (Journal of Plant Growth Regulation, 2008)

Ultrastructural and cytochemical studies on the infection process of Sclerotinia sclerotiorum in oilseed rape - L. Huang; H. Buchenauer; Q. Han; X. Zhang; Z. Kang (Journal of Plant Diseases and Protection, 2008)

Genotypic differences in leaf biochemical, physiological and growth responses to ozone in 20 winter wheat cultivars released over the past 60 years - D. K. BISWAS; H. XU; Y. G. LI; J. Z. SUN; X. Z. WANG; X. G. HAN; G. M. JIANG (Global Change Biology, 2008)
Ozone (O 3 ) concentrations in periurban areas in East Asia are sufficiently high to decrease crop yield. However, little is known about the genotypic differences in O 3 sensitivity in winter wheat in relation to year of cultivar release. This paper reports genotypic variations in O 3 sensitivity in 20 winter wheat cultivars released over the past 60 years in China highlighting O 3 ‐induced mechanisms. Wheat plants were exposed to elevated O 3 (82 ppb O 3 , 7 h day −1 ) or charcoal‐filtered air ( 3 ) for 21 days in open top chambers. Responses to O 3 were assessed by the levels of antioxidative activities, protein alteration, membrane lipid peroxidation, gas exchange, leaf chlorophyll, dark respiration and growth. We found that O 3 significantly reduced foliar ascorbate (−14%) and soluble protein (−22%), but increased peroxidase activity (+46%) and malondialdehyde (+38%). Elevated O 3 depressed light saturated net photosynthetic rate (−24%), stomatal conductance (−8%) and total chlorophyll (−11%), while stimulated dark respiration (+28%) and intercellular CO 2 concentration (+39%). O 3 also reduced overall plant growth, but to a greater extent in root (−32%) than in shoot (−17%) biomass. There was significant genotypic variation in potential sensitivity to O 3 that did not correlate to observed O 3 tolerance. Sensitivity to O 3 in cultivars of winter wheat progressed with year of release and correlated with stomatal conductance and dark respiration in O 3 ‐exposed plants. O 3 ‐induced loss in photosynthetic rate was attributed primarily to impaired activity of mesophyll cells and loss of integrity of cellular membrane as evidenced by increased intercellular CO 2 concentration and lipid peroxidation. Our findings demonstrated that higher sensitivity to O 3 in the more recently released cultivars was induced by higher stomatal conductance, larger reduction in antioxidative capacity and lower levels of dark respiration leading to higher oxidative damage to proteins and integrity of cellular membranes.

Changes in phosphorus fractions, sorption and release in Udic Mollisols under different ecosystems - C. Song; X. Z. Han; C. Tang (Biology and Fertility of Soils, 2007)

Redirecting retroviral tropism by insertion of hepatitis B virus PreS1 core peptide into the envelope - P. Qi; J.-X. Han; Y.-Q. Lu; C.-X. Wang (Archives of Virology, 2007)

Terrestrial carbon pools in southeast and south-central United States - Fengxiang X. Han; M. John Plodinec; Yi Su; David L. Monts; Zhongpei Li (Climatic Change, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Reusable immunomagnetic beads in an enzyme immunoassay - F. C. Han; J. Luo; H. F. Guo; W. H. Zhang; D. C. He; X. J. Yan (World Journal of Microbiology and Biotechnology, 2007)

Importance of point sources on regional nitrous oxide fluxes in semi-arid steppe of Inner Mongolia, China - J. Holst; C. Liu; Z. Yao; N. Brüggemann; X. Zheng; X. Han; K. Butterbach-Bahl (Plant and Soil, 2007)

Effect of Cadmium in Feed on Organs and Meat Colour of Growing Pigs - Y.-J. Tu; X.-Y. Han; Z.-R. Xu; Y.-Z. Wang; W.-F. Li (Veterinary Research Communications, 2007)

Nitrogen and carbon isotope responses of Chinese cabbage and chrysanthemum to the application of liquid pig manure - Sang-Sun Lim; Woo-Jung Choi; Jin-Hyeob Kwak; Jae-Woon Jung; Scott X. Chang; Han-Yong Kim; Kwang-Sik Yoon; Soo-Myung Choi (Plant and Soil, 2007)

Spectral reflectance and leaf internal structure changes of barley plants due to phytoextraction of zinc and cadmium - B. B. Maruthi Sridhar; F. X. Han; S. V. Diehl; D. L. Monts; Y. Su (International Journal of Remote Sensing, 2007)

Monitoring the effects of arsenic and chromium accumulation in Chinese brake fern ( Pteris vittata ) - Maruthi B. B. Sridhar; F. X. Han; S. V. Diehl; D. L. Monts; Y. Su (International Journal of Remote Sensing, 2007)

Spatial analysis for spring bloom and nutrient limitation in Xiangxi bay of three Gorges Reservoir - L. Ye; X. Q. Han; Y. Y. Xu; Q. H. Cai (Environmental Monitoring and Assessment, 2007)

Making carbon sequestration a paying proposition - Fengxiang X. Han; Jeff S. Lindner; Chuji Wang (The Science of Nature, 2007)

Effect of Bioaccumulation of Cs and Sr Natural Isotopes on Foliar Structure and Plant Spectral Reflectance of Indian Mustard (Brassica Juncea) - Yi Su; B. B. Maruthi Sridhar; F. X. Han; S. V. Diehl; D. L. Monts (Water, Air, & Soil Pollution, 2007)

Approaching chickpea quantitative trait loci conditioning resistance to Ascochyta rabiei via comparative genomics - X. Y. Bian; R. Ford; T. R. Han; T. E. Coram; E. C. K. Pang; P. W. J. Taylor (Australasian Plant Pathology, 2007)

Pacemaker currents modulated by C-type natriuretic peptide in interstitial cells of Cajal from murine small intestine - Y. Zhang; L. Hua Piao; X. Huang; Y. Fei Han; P. Zhao; L. Gao; Y. Kim; W. X. Xu (Journal of Physiology and Biochemistry, 2006)

Soil Nitrification and Denitrification Potentials in a Wheat Field Soil as Affected by Elevated Atmospheric CO2 and Rice Straw Incorporation - Y. Shi; S. Y. Wang; L. Han; J. Yue; L. X. Yang; Y. L. Wang; J. G. Zhu (Bulletin of Environmental Contamination and Toxicology, 2006)

Extent and pattern of DNA methylation alteration in rice lines derived from introgressive hybridization of rice and Zizania latifolia Griseb - Z. Y. Dong; Y. M. Wang; Z. J. Zhang; Y. Shen; X. Y. Lin; X. F. Ou; F. P. Han; B. Liu (Theoretical and Applied Genetics, 2006)

Genetic diversity of avian infectious bronchitis coronavirus strains isolated in China between 1995 and 2004 - S. W. Liu; Q. X. Zhang; J. D. Chen; Z. X. Han; X. Liu; L. Feng; Y. H. Shao; J. G. Rong; X. G. Kong; G. Z. Tong (Archives of Virology, 2006)

Leaching of Copper from an Industrial Sludge Applied on a Soil Column - J. Xu; S. Dai; X. Han; S. Sun; P. Zhang (Bulletin of Environmental Contamination and Toxicology, 2006)

Rapid Determination of Mercury in Plant and Soil Samples Using Inductively Coupled Plasma Atomic Emission Spectroscopy, a Comparative Study - Fengxiang X. Han; W. Dean Patterson; Yunju Xia; B. B. Maruthi Sridhar; Yi Su (Water, Air, & Soil Pollution, 2006)

Interactions Between High pH and Iron Supply on Nodulation and Iron Nutrition of Lupinus albus L. Genotypes Differing in Sensitivity to Iron Deficiency - C. Tang; S. J. Zheng; Y. F. Qiao; G. H. Wang; X. Z. Han (Plant and Soil, 2006)

A genetic linkage map for azuki bean [Vigna angularis (Willd.) Ohwi & Ohashi] - O. K. Han; A. Kaga; T. Isemura; X. W. Wang; N. Tomooka; D. A. Vaughan (Theoretical and Applied Genetics, 2005)

Leaching Behavior of Copper (II) in a Soil Column Experiment - J. Xu; X. Han; S. Sun; F. Meng; S. Dai (Bulletin of Environmental Contamination and Toxicology, 2005)

Mycobacterium lentiflavum, a recently identified slow-growing mycobacterial species: clinical significance in immunosuppressed cancer patients and summary of reported cases of infection - A. Safdar; X. Y. Han (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Inhibiting the Sexual Behavior of Female Cotton Bollworm Helicoverpa armigera - W. X. Dong; B. Y. Han; J. W. Du (Journal of Insect Behavior, 2005)

Phosphorus characteristics correlate with soil fertility of albic luvisols - X. Z. Han; C. Tang; C. Y. Song; S. Y. Wang; Y. F. Qiao (Plant and Soil, 2005)

Effects of Acid Precipitation and Aluminum on Carbohydrate Metabolism in Mycorrhizae of Pinus massioniana - J. K. Tan; F. X. Kong; H. S. Cao; Y. Yu; X. B. Han (Bulletin of Environmental Contamination and Toxicology, 2005)

Time Course Biochemical Responses of Green Algae Scenedesmus obliquus to Aluminum and Low pH - S. A. Jusu; F. X. Kong; B. Q. Qing; J. K. Tan; X. B. Han (Bulletin of Environmental Contamination and Toxicology, 2004)

Flood control and land use management in Mengwa retention area, Huai River Basin - Han Ruiguang; F. X. Suryadi (Irrigation and Drainage, 2004)
Retention areas have a very important role in flood alleviation in the Huai River Basin. With economic and societal development the former retention areas have been developed and some of them even became very important urban areas. When floods come, there is a lot of damage. The government has realized that the flood control standards in the whole river basin are low and has made a plan to increase flood control standards for the Mengwa retention area. The design water level will be 28.00 m+MSL at Runheji. In light of this the use of the Mengwa retention area needs to be considered. To arrive at decisions that reduce flood damage, one should take into account the following uncertainties: the river discharge, the flood damage given the discharge, the downstream water level given the discharge, and the costs of constructing embankments and dredging the river. By using the DUFLOW model and a GIS model, the present situation and the alternative development options have been analysed. How to use the Mengwa retention area is also discussed. Copyright © 2004 John Wiley & Sons, Ltd.

Genetic mapping of EST-derived microsatellites from the diploid Gossypium arboreum in allotetraploid cotton - Z.-G. Han; W.-Z. Guo; X.-L. Song; T.-Z. Zhang (Molecular Genetics and Genomics, 2004)

Nonylphenol Induced Apoptosis in Rat Testis Through the Fas/FasL Pathway - X. Han; Z. Tu; X. Wang; S. Shen; Y. Hou (Bulletin of Environmental Contamination and Toxicology, 2004)

Distribution, transformation and bioavailability of trivalent and hexavalent chromium in contaminated soil - Fengxiang X. Han; Yi Su; B. B. Maruthi Sridhar; David L. Monts (Plant and Soil, 2004)

Activation of a rice endogenous retrotransposon Tos17 in tissue culture is accompanied by cytosine demethylation and causes heritable alteration in methylation pattern of flanking genomic regions - Z. L. Liu; F. P. Han; M. Tan; X. H. Shan; Y. Z. Dong; X. Z. Wang; G. Fedak; S. Hao; Bao Liu (Theoretical and Applied Genetics, 2004)

Infections by the Yeast Kodomaea ( Pichia ) ohmeri : Two Cases and Literature Review - X. Y. Han; J. J. Tarrand; E. Escudero (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Effect of temperature on the pathogenicity of entomopathogenic nematodes (Steinernema and Heterorhabditis spp.) to Delia radicum - S. Chen; J. Li; X. Han; M. Moens (BioControl, 2003)

Assessment of global industrial-age anthropogenic arsenic contamination - Fengxiang X. Han; Yi Su; David L. Monts; M. John Plodinec; Amos Banin; Glover E. Triplett (The Science of Nature, 2003)

Helix 6 of tBid is necessary but not sufficient for mitochondrial binding activity - X. Hu; Z. Han; J. H. Wyche; E. A. Hendrickson (Apoptosis, 2003)

Effect of Nonylphenol on Apoptosis of Sertoli Cells in Vitro - X. Wang; X. Han; Y. Hou; G. Yao; Y. Wang (Bulletin of Environmental Contamination and Toxicology, 2003)

Industrial age anthropogenic inputs of heavy metals into the pedosphere - Fengxiang X. Han; Amos Banin; Yi Su; David L. Monts; John M. Plodinec; William L. Kingery; Glover E. Triplett (The Science of Nature, 2002)

Response-Surface Analysis for the Inhibition Toxicity of Benzene Derivatives to Yeast Saccharomyces cerevisiae - X. Wang; Y. Wang; X. Dai; L. Wang; S. Han (Bulletin of Environmental Contamination and Toxicology, 2002)

Comparative Inhibition and Quantitative Structure-Activity Relationships (QSARs) of Substituted Phenols to Germination Rate of Cucumis sativus - X. Wang; X. Yang; Y. Wang; L. Wang; S. Han (Bulletin of Environmental Contamination and Toxicology, 2002)

An Assessment of the RAIM Performance of a Combined Galileo/GPS Navigation System Using the Marginally Detectable Errors (MDE) Algorithm - W. Y. Ochieng; K. F. Sheridan; K. Sauer; X. Han; P. A. Cross; S. Lannelongue; N. Ammour; K. Petit (GPS Solutions, 2002)

Correlation of Reversed-Phase Retention Factors for α-Branched Phenylsulfonyl Acetates with Octanol/Water Partition Coefficients and Quantum Chemical Descriptors - X. Liu; D. Wei; C. Wu; S. Han; L. Wang (Bulletin of Environmental Contamination and Toxicology, 2001)

Structure-phytotoxicity relationship: Comparative inhibition of selected nitrogen containing aromatics to root elongation of Cucumis sativus - X. Wang; Y. Dong; S. Han; L. Wang (Bulletin of Environmental Contamination and Toxicology, 2000)

Quantitative Structure-Activity Relationships for the Toxicity to the Tadpole Rana japonica of Selected Phenols - X. Wang; Y. Dong; S. Xu; L. Wang; S. Han (Bulletin of Environmental Contamination and Toxicology, 2000)

Quantitative Structure-Activity Relationships for the Toxicity to the Tadpole Rana japonica of Selected Phenols - X. Wang; Y. Dong; S. Xu; L. Wang; S. Han (Bulletin of Environmental Contamination and Toxicology, 2000)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.